THE EFFECT OF MONETARY POLICY REGIME ON THE DEVELOPMENT OF THE ECONOMY - Qaiyrzhan, Maqsat (Nazarbayev University Graduate School of Business, 2024)
This work investigates how the Kazakhstani economy is affected by the monetary regimes, given the susceptibility to volatile oil prices and foreign capital flows. Dynamic Stochastic General Equilibrium Model (DSGE) was utilized to analyze the effect of shocks on real GDP, consumption, investment, wages, exports, imports, prices, and real exchange rates. Next, the effectiveness of fixed exchange rates, inflation targeting, strict inflation targeting, and hybrid inflation targeting monetary policy regimes in smoothing the impulse of shocks on the above-mentioned variables. The results suggest that hybrid inflation targeting regime has relatively better performance.
Keywords: Economy; DSGE; Monetary policy regime; inflation targeting; Type of access: Open